Lacanian Psychoanalysis and the Possibility of Re-invention of the Political: A Critical Review of Lacan and the Political - Aliashraf Nazari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Psychological and political theories are the mission of understanding individual and collective behaviors in the context of political life. Over the past two decades, the analysis of the psychoanalytic dimensions of politics with the focus of this discussion on how to talk about the relationship between politics and psychology has attracted many scholars. Meanwhile, Jacques Lacan is one of the most prominent psychoanalysts who tried to bridge psychological and philosophical issues, anthropology and linguistics, and some implications could be found for linking psychological aspects and politics to his intellectual system. The main questions of the article include how can a political reading of Jacques Lacan's ideas be? And, what will be the analytical implications of the link between psychology and politics in Lacan's theory? The answer is that the Lacan political-psychological theory, through the discussion of the real and symbolic, knowledge and experience, the political and social, on the one hand, sets limits, and on the other hand, brings us innovative possibilities. These are areas of tension and facilities, limitations and aspirations. The main focus of this paper is to introduce, criticize, and evaluate Lacan and the political book.